IC 8430 Disposal Of Solid Wastes From Coal Mining In Washington, Oregon, And Montana - M. R. Geer (The National Institute for Occupational Safety and Health (NIOSH), 1969)
The Bureau of Mines surveyed the solid wastes that have accumulated from coal mining in Washington, Oregon, and Montana. Location, amount, character, and condition were determined, and both economic and environmental factors were considered. Areas covered by waste comprise 800 acres in Washington, 5 acres in Oregon, and 1,200 acres in Montana. In a few cases waste is being utilized, particularly cinder from burned refuse dumps, as fill in road construction and as a ceramic raw material. It is estimated that wastes deriving from coal mined for electric power generation by 1974 may amount to 3 million tons of washery refuse, 2.7 million tons of fly ash, and 1,000 acres of spoil banks.